Uprooted : a memoir about what happens when your family moves back - Chan, Ruth, 1980- (Roaring Brook Press, a division of Holtzbrinck Publishing Holdings Limited Partnership, 2024)
"Ruth is moving to Hong Kong. And she is not happy about it. She's going to miss her best friends, her favorite ketchup-flavored potato chips, and Toronto, the only home she's ever known. Her mom is excited to reunite with her family, but it's not the same for Ruth. In Hong Kong, her classes are harder, her Cantonese isn't good enough, and her parents are never around. Ruth feels lonely and completely unrooted. But as Ruth's dad tells stories about her family -- how they found strength and courage to survive the most difficult times -- Ruth realizes that she too can be strong. Gradually, she puts down roots, knowing she can always find home, wherever she is." --